2016
DOI: 10.1007/s00520-016-3386-9
|View full text |Cite|
|
Sign up to set email alerts
|

Role of olanzapine in chemotherapy-induced nausea and vomiting on platinum-based chemotherapy patients: a randomized controlled study

Abstract: Olanzapine was found to be effective as add-on in the control of CINV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 41 publications
1
62
0
Order By: Relevance
“…The age range of the participants included in RCTS was 18-8920-24,26,29,31,32 and not reported in three of the trials 25,27,28. One of the trials reported age in median (SD) 30. Seven of the trails reported that either 5-HT 3 receptor antagonist and/or dexamethasone with olanzapine compared with the same regimen without olanzapine24-30 and 6 of trials reported that olanzapine with NK-1 receptor antagonists (either aprepitant or fosaprepitant) containing regimen 20-23,31,32.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The age range of the participants included in RCTS was 18-8920-24,26,29,31,32 and not reported in three of the trials 25,27,28. One of the trials reported age in median (SD) 30. Seven of the trails reported that either 5-HT 3 receptor antagonist and/or dexamethasone with olanzapine compared with the same regimen without olanzapine24-30 and 6 of trials reported that olanzapine with NK-1 receptor antagonists (either aprepitant or fosaprepitant) containing regimen 20-23,31,32.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the trails reported that either 5-HT 3 receptor antagonist and/or dexamethasone with olanzapine compared with the same regimen without olanzapine24-30 and 6 of trials reported that olanzapine with NK-1 receptor antagonists (either aprepitant or fosaprepitant) containing regimen 20-23,31,32. Eleven trials reported olanzapine administered at a dose in 10 mg/day orally20-26,28,30-32, whereas two trials reported olanzapine administered in a 5 mg/day orally 27,29. Nine of the trials reported participants receiving HEC20-23,25,26,30,31,32 and four studies included patients receiving combination of MEC/HEC 24,27-29.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations